2022
DOI: 10.1136/bmjopen-2020-046172
|View full text |Cite
|
Sign up to set email alerts
|

Postcholecystectomy diarrhoea rate and predictive factors: a systematic review of the literature

Abstract: ObjectivesCholecystectomy is one of the most common surgical procedures performed worldwide to treat gallstone-related disease. Postcholecystectomy diarrhoea (PCD) is a well-reported phenomenon, however, the actual rate, predictive factors and mechanism of action have not been well determined. A systematic review was undertaken to determine the rate and predictive factors associated with diarrhoea in the postcholecystectomy setting.MethodsThe review was conducted according to the Preferred Reporting Items for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…The prospective study design allows for systemic evaluation of the changes in major FGID symptoms after cholecystectomy using validated questionnaires and the Rome III criteria. Previous studies regarding post-cholecystectomy syndrome were retrospective or did not include a control group (40). Second, patients who underwent emergency surgery for acute cholecystitis or biliary obstruction and those who underwent open cholecystectomy were excluded from this study to avoid the effects of surgical stress.…”
Section: Discussionmentioning
confidence: 99%
“…The prospective study design allows for systemic evaluation of the changes in major FGID symptoms after cholecystectomy using validated questionnaires and the Rome III criteria. Previous studies regarding post-cholecystectomy syndrome were retrospective or did not include a control group (40). Second, patients who underwent emergency surgery for acute cholecystitis or biliary obstruction and those who underwent open cholecystectomy were excluded from this study to avoid the effects of surgical stress.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 3 ] Nevertheless, postcholecystectomy syndrome (PCS) may occur weeks or months after cholecystectomy and manifests with clinical symptoms such as diarrhea, abdominal pain, and bloating. In particular, postcholecystectomy diarrhea (PCD) is a relatively well-known clinical complication [ 4 , 5 ] characterized by a prolonged course, recurrence, and persistence, which significantly affects the quality of life of patients and even causes a portion of the population to develop disability. [ 6 ] PCD is highly prevalent and protracted.…”
Section: Introductionmentioning
confidence: 99%
“…A previous review reported an average prevalence of 13.3% (2.1%–57.2%), although with the limitation of various follow-up times. [ 4 ] The 2020 Canadian Chronic Diarrhea Guidelines highlight cholecystectomy as a risk factor for chronic diarrhea. [ 7 ] In addition, Ribas et al [ 8 ] found that >50% of patients had abnormal bowel habits after cholecystectomy, of which 23% had unrelieved symptoms after 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 BAD can occur without known underlying pathophysiology or be secondary to other conditions such as inflammatory bowel diseases, cholecystectomy, celiac disease, intestinal resection, or damage after radiotherapy. 1,5 In Denmark, the disease is diagnosed with the gold standard ⁷⁵seleniumhomotaurocholic acid (SeHCAT) test, where the 7-day retention of orally administered SeHCAT is measured. Even though the SeHCAT test is a well-known and accepted diagnostic tool, [6][7][8] BAD was not registered as a diagnosis in WHO's International Classification of Diseases Version 10 (ICD10) before 2021.…”
Section: Introductionmentioning
confidence: 99%